Cardioversion in Infantile Atrial Flutter - Ara, Andaleeb; Akhtar, Khurram; Rafique, Saima; Farhan, Mohammad Asad; Ahmed, Tufail (Pakistan Armed Forces Medical Journal, 2022)
Atrial flutter (AFL) is a rare arrhythmia in neonatal and infantile period. Potentially, AFL might lead to severe morbidity and even a fatal outcome. However it can have a good prognosis with early diagnosis and prompt appropriate treatment. Synchronized electrical cardioversion or transoesophageal atrial overdrive pacing is recommended in both stable and unstable cases. Antiarrhythmic drugs can be tried in stable newborns though the sinus rhythm takes some time to return to normal.Excellent prognosis has been noted in newborns and infants having AFL after sinus rhythm has been restored. The risk of recurrence is low and prolonged antiarrhythmic therapy is less likely to be required. However follow-up after discharge is essential to look for any possibility of recurrent arrhythmia and possible untoward effects of treatment.